(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article discusses the basic features of using Identity Management technology. Accordingly, to manage personal data in IT, large companies will be forced to implement specialized IDM-class systems to manage information about users of their corporate systems. If earlier there was a certain shortage of qualified personnel in this area, now this shortage will take on catastrophic proportions, since thunder has struck and the peasant must begin to be baptized.